“Pasangan Minimal” Fonem Alat “Permainan Bahasa” - Setyadi, Ary (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The phoneme “minimal pair” data can be used as a “language games” tool, because the notion of “language games” is: the efforts made by language speakers in “playing with” language, especially words, for specific purposes/interests. Based on existing references, the problem of the “minimal pair” phoneme as a “language game” tool has never been used as a separate research object, so it is interesting to study. The data is obtained by listening and different/contrasting meaning with the method of recording/recording. The type of data is secondary, because more data is found in several references that discuss Indonesian phonology. Data analysis based on the application of phonology linguistic theory, phonemic subfields. The final results of the study found five kinds of “language gamesing” patterns, namely: 1) patterned: one vowel phoneme vs. one vowel phoneme, 2) patterned: two vowel phonemes vs. two vowel phonemes, 3) patterned: one vowel phoneme vs. one diphthong phoneme, 4) patterned: one consonant phoneme vs. one consonant phoneme, and 5) patterned: two consonant phonemes vs. two consonant phonemes.